Bioatividade de óleos essenciais e compostos químicos majoritários para o ácaro Oligonychus ilicis (McGregor, 1917) (Acari: Tetranychidae) e toxicidade para o predador Euseius concordis (Chant, 1959) (Acari: Phytoseiidae) - Lopes, Nathan Jhon Silva (2020)
Among the organisms that are considered coffee pests, the most important are the mites, the main one is the coffee mite Oligonychus ilicis (McGregor, 1917) (Acari: Tetranychidae). This arthropod is present in the main coffee producing regions of Brazil, such as the states of Minas Gerais, São Paulo and mainly in the region of Espírito Santo state, the main producing state of Conilon coffee. The attack of these mites usually occurs in the field, reaching the entire crop. There are natural enemies associated with this pest, such as the mite Euseius concordis (Chant, 1959) (Acari: Phytoseiidae), however, chemical control, has been the most used method for control. However, synthetic pesticides can cause negative impacts on the environment and man if used incorrectly, and therefore, research is needed to obtain other more effective control measures with less environmental impact. In order to minimize the undesirable effects of synthetic pesticides, pest control with plant oils has become a promising, low-cost and safe alternative for users and consumers. Thus, the objective of the present study was to evaluate the bioactivity of essential oils from plants of the Lauraceae, Lamiaceae, Myrtaceae and Rutaceae families for phytophagous mite O. ilicis; select the most promising essential oils and characterize them chemically through GC-MS and evaluate the effects of essential oils and major compounds on the predatory mite E. concordis. All oils were initially tested at a concentration of 10 mg / ml, in repellency there was a highlight in oils of the genus Citrus spp. while in topical application the promising oils were Cinnamomum cassia (cinnamon) and Thymus vulgaris (thyme), its major chemical components were cinnamaldehyde <E> and ortho-cymene / carvacrol respectively. Lethal concentrations show that T. vulgaris oil (LC50 = 3.2 mg / ml) was more toxic than C. cassia oil (LC50 = 4.9 mg / ml), and in extra parameters: residual toxicity, ovicidal effect, fumigant toxicity and in immature these oils were also effective. The toxicity tests showed that the cinnamaldehyde compound <E> was responsible for the acaricidal activity of the C. cassia oil, whereas the carvacrol compound did not have an acaricidal performance, suggesting that there is synergism between the components of the T. vulgaris oil for it to occur toxicity. The essential oils of C. cassia and T. vulgaris and the major compounds tested were not selective to the predatory mite E. concordis, thus suggesting that management techniques be studied and implemented for the adequate control of the pest without affecting the non-target organism, as well as future studies should focus on the mode of action of these substances to contribute to the integrated management of coffee pests.